2021
DOI: 10.1080/01441647.2021.1895361
|View full text |Cite
|
Sign up to set email alerts
|

Cyclists’ exposure to atmospheric and noise pollution: a systematic literature review

Abstract: Cyclists constitute a population particularly exposed to atmospheric and noise pollution in urban environments; at the same time, they contribute to its reduction. For about ten years now, more and more studies have been completed to assess cyclists' exposure, comparing this mode of transportation with others, quantifying its impacts in term of individual and collective health, understanding cyclists' perceptions regarding their exposure, etc. Though some literature reviews have examined some of these specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 108 publications
(195 reference statements)
2
26
0
Order By: Relevance
“…Micromobility modes such as bicycles, e-scooters, lightweight PMDs, and walking can help to minimize pollution and noise in cities. However, these modes operate in crowded traffic areas, so the users are still exposed to particles and multiple sounds [13]. The health organizations even suggest that people with respiratory and cardiovascular problems should avoid outdoor activity if the concentration of specific pollutants is high [34].…”
Section: Environmental and Health Indicators-the Users' Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…Micromobility modes such as bicycles, e-scooters, lightweight PMDs, and walking can help to minimize pollution and noise in cities. However, these modes operate in crowded traffic areas, so the users are still exposed to particles and multiple sounds [13]. The health organizations even suggest that people with respiratory and cardiovascular problems should avoid outdoor activity if the concentration of specific pollutants is high [34].…”
Section: Environmental and Health Indicators-the Users' Perspectivementioning
confidence: 99%
“…At once, reducing polluting particles by replacing motor vehicles is not the only crucial metric. From an environmental and health angle, users' exposure when traveling through highly polluted and noisy cities should be equally considered [13]. A user can opt for an e-bicycle or a traditional, more intense, and healthier one.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants cycled alone on predefined routes for 87 h and for a total of 1199 km. This extensive mobile data collection allows us to maximize spatial coverage of the study area and ensure a diversity of urban settings [43]. All data collection days started and ended at the university, thus allowing researchers to stay in touch with the participants, provide support when needed and supervise the data acquisition process closely.…”
Section: Data 221 Primary Data: An Extensive Mobile Data Collectionmentioning
confidence: 99%
“…Public transit usage by the public can increase the perceived behavioral control to maintain good health and the environment. Additionally, the concept of perceived behavioral control can refer to self-evaluation in terms of the environmental, health, and other issues which are contributing to pollution and congestion matter [47]. Previous studies [48] revealed different socio-demographic factors such as race, age, education level, and significant income have a relationship with awareness of using public transport on using public transportations.…”
Section: Perceived Behavioral Controlmentioning
confidence: 99%